Patient Satisfaction with Dental Services: A Cross-Sectional Studyof Five Public Sector Dental Hospitals in Karachi - Sana Iqbal; Sheeza Shah; Bismillah Naeem; Sameera Kazi; Atiya Noor; Mirza Hamid Baig (Annals of Abbasi Shaheed Hospital and Karachi Medical & Dental College)
Objective: This study assessed patient satisfaction with dental facilities, services, and treatment while identifying key areas for improvement in five public sector dental hospitals in Karachi, Pakistan. Methods: This multi-centered cross-sectional study was conducted at five public sector dental teaching hospitals over three months. A random sampling technique was used to recruit 530 patients (106 from each hospital). The inclusion criteria consisted of patients aged 18 to 70 years with dental conditions who visited the hospitals during the data collection period and consented to participate. Patients receiving treatment at private clinics or hospitals were excluded. A structured, standardized, and validated self-administered patient satisfaction questionnaire, adapted from Othman L.’s questionnaire, was used for data collection. The 32-item questionnaire covered five domains: socio-demographic characteristics, system/administrative efficiency, hospital facilities, patient-dental relationship, and overall satisfaction. Responses were recorded using a 3-point Likert scale (1 = disagree, 2 = uncertain, 3 = agree). A pilot study was conducted before the main study to assess the validity and reliability of the questionnaire. Data were analyzed using SPSS version 23, with descriptive and inferential statistics applied to determine significant associations. Results: Of the 530 participants, 61.7% were female, and the majority expressed satisfaction with dental services. Significant associations (p < 0.05) were found between gender and key satisfaction parameters, such as perceptions of professionalism and dental treatment quality. Among the hospitals, Civil Hospital scored the lowest, indicating the greatest need for improvements, while DIDC received the highest satisfaction score. Conclusion: The study concluded that while most patients were satisfied with the dental services provided at public sector hospitals in Karachi, specific areas still require improvement. These include implementing effective appointment reminder systems, reducing wait times, enhancing hospital facilities including pleasant ambient features—and improving staff-patient interactions. Notably, Civil Hospital scored the lowest in-patient satisfaction, highlighting a need for targeted improvements to elevate patient experiences and overall service quality